Hubungan Character Strength Mahasiswa Dengan Preferensi Kepribadian Dosen Fakultas Ushuluddin dan DakwahH IAIN Kediri - Muzakki, Imron; Sayekti, Fatma Puri; Fitriah, Lailatul (Universitas Trunojoyo Madura, 2025)
The personality aspect of lecturers remains a significant concern at the Faculty of Ushuluddin and Dakwah (FUDA), IAIN Kediri. Lecturer evaluations by students over the past year indicate that this aspect received the lowest scores compared to pedagogic, professionalism, and social aspects. This study aims to: a) identify the dominant character strengths of FUDA students, b) describe students' preferences for lecturers' personality types, and c) examine the relationship between student character strengths and their personality preferences in lecturers. A quantitative approach using a survey method was employed, with cluster random sampling based on seven study programs. A total of 315 students from semesters 2, 4, and 6 participated. Instruments included the Character Strength Scale by Garvin (based on Peterson and Seligman) and the Lecture Preference Questionnaire (LPQ), adapted from the NEO-Personality Inventory. Results revealed wisdom and knowledge (27%) as the most dominant character strength, while temperance (9%) was the lowest. Most students preferred lecturers with openness (29%) and least preferred neuroticism (5%). Bivariate correlation showed positive relationships between all character strengths and preferred lecturer traits such as openness, conscientiousness, extraversion, and agreeableness, and a negative relationship with neuroticism. These findings suggest the importance of strengthening both student character and lecturer personality through targeted development programs.